2021
DOI: 10.3390/en14092519
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of Agri- and Aquaculture Residues via Biogas Production for Enhanced Industrial Application

Abstract: Climate changes are nowadays reality and affect all aspects of everyday life. One of the places where these changes influence the society the most is the Brazilian Ceará region and Jaguaribara basin that suffer long-lasting, devastating drought cycles. They have a dramatic negative impact on local economy, forcing change in business models. This work presents the valorisation of wastes and residues from local fish, prawns, and the vegetable-cultivation industry via biogas production forced to adapt to these ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In businesses providing purposeful sufficiency in circular fertilizers, the entrepreneurs aim to become self-sufficient in the sense of being capable to provide the most essential resources by themselves, without prioritizing profit maximization. Ximenes et al (2021) analyze a case study of a company that anaerobically digests fish, oil and vegetable residues in the Northeast of Brazil. While a direct increase in profits may not be visible in the short term, the company will build energy independence and security as well as a positive brand image (Ximenes et al, 2021).…”
Section: Purposeful Su Ciencymentioning
confidence: 99%
See 2 more Smart Citations
“…In businesses providing purposeful sufficiency in circular fertilizers, the entrepreneurs aim to become self-sufficient in the sense of being capable to provide the most essential resources by themselves, without prioritizing profit maximization. Ximenes et al (2021) analyze a case study of a company that anaerobically digests fish, oil and vegetable residues in the Northeast of Brazil. While a direct increase in profits may not be visible in the short term, the company will build energy independence and security as well as a positive brand image (Ximenes et al, 2021).…”
Section: Purposeful Su Ciencymentioning
confidence: 99%
“…Ximenes et al (2021) analyze a case study of a company that anaerobically digests fish, oil and vegetable residues in the Northeast of Brazil. While a direct increase in profits may not be visible in the short term, the company will build energy independence and security as well as a positive brand image (Ximenes et al, 2021). The authors argue that the adoption of small-scale biogas and fertilizer production technologies can drive small agro-industrial companies and their sector to transform (Ximenes et al, 2021).…”
Section: Purposeful Su Ciencymentioning
confidence: 99%
See 1 more Smart Citation
“…There is no extensive experience of applying of digestate in Russia, but based on the application rate of N by digestates [31], it can be concluded that the use of digestates is similar to the use of manure, which is common for Russian farms. The experience of other countries (e.g., Brazil [39]) shows that the use of any organic waste for electricity generation can be considered from the point of view of environmental benefits like reducing waste in landfills, increasing economic efficiency and stability of production by saving energy costs, reducing transport fuel volumes and reducing CO2 emissions [39]. However, the only experience in the future will allow to adapt to the use of new organic fertilizers on Russian farms, taking into account the peculiarities of farming in Russia in different climatic zones and on different soils.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ximenes et al (2021) proved that industrial waste and residue valorisation through biogas production is a feasible solution for a specific industrial scenario dealing with new socio-economic challenges [11]. This author presents the valorisation of wastes and residues from local fish, prawns and the vegetable-cultivation industry via biogas production forced to adapt to these new circumstances.…”
Section: Introductionmentioning
confidence: 99%